Development and psychometric testing of a scale for diet self-management among urban residents in China: a cross-sectional study - Lai Wei; Li Zhou; Yalin Chu; Yuhong Tang (BMJ Open)
Objective Design The diet self-management scale (DSE-MS) items were identified and evaluated by literature and guideline review, expert consultation and pilot testing. Factor structure was tested by randomly dividing the sample into two equal groups for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The scale was further tested for internal consistency, convergent validity, discriminant validity and known-group validity.Setting A city in China.Participants A total of 724 urban residents from a city in China participated in this study in 2023.Results The final DSE-MS included 45 items and showed good internal consistency with a Cronbach’s alpha coefficient of 0.961. EFA identified 6 dimensions explaining 67.89% of the total variance: cognition (11 items), microenvironment (12 items), macroenvironment (4 items), safety management (7 items), nutrition management (6 items) and environment management (5 items). The CFA showed a good model fit of the six-dimension scale: χ2/df=1.8878, root mean square error of approximate=0.0496, Comparing Fit Index=0.9425, Incremental Fit Index=0.9428, Tucker-Lewis Index=0.9369 and standard root mean square residual=0.0525. Convergent validity was supported by high composite reliability (CR=0.89–0.96) and average variance extracted (AVE=0.58–0.72), while discriminant validity was confirmed by higher AVE estimates than the squared interconstruct correlations. The DSE-MS scores varied by various sample characteristics, verifying the known-group validity.Conclusion The 6-factor 45-item DSE-MS had good psychometric properties assessing diet self-management among urban citizens. The scale can guide future intervention programmes to improve diet self-management and evaluate the intervention effect. Further validation of the DSE-MS in other populations in other areas is needed to verify its wide application.